Multisystem inflammatory syndrome associated with SARS-CoV-2 in pediatrics: A narrative review of diagnosis and treatment (Research, Society and Development, 2024)
During the COVID-19 pandemic, initial studies investigating the impact of this disease on the pediatric population demonstrated evidence of little clinical impact in this population. However, the emergence of Multisystem Inflammatory Syndrome associated with SARS-CoV-2 (SIM-P) with more serious symptomatic repercussions, as well as a poor prognosis, raised alarm in the pediatric community in favor of developing a diagnostic and therapeutic consensus regarding the new syndrome. Given the relevance of the subject, this study proposes to visit review articles, guidelines, meta-analyses and clinical studies with the aim of discussing the best definitions regarding the multisystemic condition, as well as management. Through manual search in databases indexed to Pubmed, with the following descriptors: “MISC associated with COVID-19” and “treatment” in English. Both being searched with the Boolean “AND”, 29 articles were definitively chosen. Realizing the urgent need to define what SIM-P would be, as well as guide the diagnosis and treatment of cases, we used the best criteria to define this new clinical condition. Furthermore, this narrative review aims to contribute to the study of SIM-P associated with SARS-CoV-2 through a critical analysis of the literature, highlighting the consensus on its diagnosis and treatment.